ATIM-37. PHASE II, OPEN-LABEL, SINGLE ARM, MULTICENTER STUDY OF AVELUMAB WITH HYPOFRACTIONATED RADIATION (HFRT) FOR ADULT PATIENTS WITH SECONDARILY TRANSFORMED IDH-MUTANT GLIOBLASTOMA (GBM). (11th November 2019) - Kurz, Sylvia; Silverman, Joshua S; Hochman, Tsivia; Nayak, Lakshmi; Arrillaga-Romany, Isabel; Lee, Eudocia; Patel, Amie; Delara, Malcolm; Hsu, Fraustina; Imtiaz, Tooba; Magnelli, Lori; Taylor, Jennie; et al.
Abstract: BACKGROUND: There is no effective therapy for patients (pts) with IDH -mutant gliomas that progress after RT and chemotherapy. At time of progression, these tumors have often transformed to glioblastoma (GBM) and have increased numbers of somatic mutations, i.e. have a "hypermutator phenotype". We hypothesized that there is synergistic efficacy of Avelumab (anti-PD-L1) combined with HFRT in pts with secondarily transformed IDH -mutant GBMs. Safety-lead-in results will be presented. METHODS: This is a phase II, open-label, single-arm, multicenter study of Avelumab with HFRT in adults with transformed IDH -mutant GBM who previously received RT and TMZ and/or PCV. All pts received Avelumab 10 mg/kg IV followed at Day 8 by HFRT (25 Gy in 5 daily 5-Gy fractions) and then Avelumab 10 mg/kg IV every 2 weeks. A 3 + 3 design was used for a 6-patient safety-lead-in cohort. Adverse events were recorded according to CTCAE. RESULTS: Six pts (F=4, M=2) with a median age= 45.5 yrs (range 31.5–54.4 yrs) were enrolled in the safety-lead-in cohort. No DLT was observed. Grade ≥ 3 AEs included increased cerebral edema (3 pts), hyponatremia (1 pt) and worsening hemiparesis (3 pts). Grade ≤ 2 AEs included nausea, hypothyroidism, lymphopenia, thrombocytopenia, transaminase elevation, and fever/chills. Median follow-up time was 8.9 mo. Best treatment response was SD in 1 patient. At time of last follow-up all pts have discontinued treatment for PD. Median PFS was 4.2 mo (range 1.4–5.7). Median OS was 10.1 (range 6.8–21+) mo. 4 pts (67%) died, 2 pts remain alive in follow-up at 6.9 and 21.6 months after treatment initiation. The study was closed after the safety lead-in completed enrollment due to slow accrual. CONCLUSIONS: Avelumab combined with HFRT was tolerable without dose-limiting toxicity in this safety-lead-in cohort of adult patients with transformed IDH -mutant GBM. Further studies are necessary to determine efficacy of this treatment regimen.